2012
DOI: 10.1111/j.1399-0004.2012.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of informed consent for individual genome sequencing on relevant knowledge

Abstract: Increasing availability of individual genomic information suggests that patients will need knowledge about genome sequencing to make informed decisions, but prior research is limited. In this study, we examined genome sequencing knowledge before and after informed consent among 311 participants enrolled in the ClinSeq™ sequencing study. An exploratory factor analysis of knowledge items yielded two factors (sequencing limitations knowledge; sequencing benefits knowledge). In multivariable analysis, high pre-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 35 publications
3
120
0
1
Order By: Relevance
“…Our prior work has indicated that individuals with limited health literacy may be more interested in receiving an assessment of genomic risk based on genetic testing than those with higher health literacy (Kaphingst et al, 2015), and other researchers have found that genetics-related literacy may impact how patients evaluate the utility of genetic testing (Hooker et al, 2014). Assessing knowledge of the benefits of genetic technologies separately from knowledge of the limitations may be important to understand the association between health literacy and knowledge (Kaphingst, Facio, et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Our prior work has indicated that individuals with limited health literacy may be more interested in receiving an assessment of genomic risk based on genetic testing than those with higher health literacy (Kaphingst et al, 2015), and other researchers have found that genetics-related literacy may impact how patients evaluate the utility of genetic testing (Hooker et al, 2014). Assessing knowledge of the benefits of genetic technologies separately from knowledge of the limitations may be important to understand the association between health literacy and knowledge (Kaphingst, Facio, et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…We designed a 100-item survey comprised largely of validated psychosocial measures from the behavioural health literature, including items from the Behavioral Risk Factor Surveillance System (2014),10 the multidimensional health locus of control scale11 and a scale measuring knowledge about the capabilities and limitations of genomic sequencing 12. We collected standard demographic variables and assessed previous experience with genetic testing, health literacy,13 self-reported health status14 and subjective assessment of discretionary income 15.…”
Section: Methodsmentioning
confidence: 99%
“…It is also because we have much to learn about the genes we will be sequencing and the gene variants we find.” The informed consent also stated that, “We may find gene variants that are novel and of uncertain clinical importance…We will only report this type of gene variant to you if we can learn enough about it to make us believe that it can cause or contribute to disease.” Participants completed the informed consent process with a trained staff member. Research among a different subset of ClinSeq ® respondents demonstrated overall improvement in knowledge of the limitations of sequencing following the informed consent procedure, although accurate understanding was not universal (Kaphingst et al, 2012). The National Human Genome Research Institute’s Institutional Review Board reviewed and approved the study.…”
Section: Methodsmentioning
confidence: 99%